Analisis Faktor Yang Mempengaruhi Kepatuhan Penggunaan Alat Pelindung Diri (APD) di Instalasi Gizi RSUD Kota Salatiga - Wardana, Agung Setya; Marfuah, Dewi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) ITS PKU Muhammadiyah Surakarta, 2021)
The hospital nutrition service program aims to improve the quality of hospital services through the provision of food. The quality of the food provided is in accordance with the nutritional value requirements of the hospital. To achieve these conditions requires knowledge and skills ranging from food procurement, production processes, to food evaluation. The production process is a vital stage so that the staff in the Nutrition Installation must have a high level of compliance in the use of PPE. The results of these observations can be used to evaluate the quality of the food produced by the nutrition installation. The research method is observation carried out using a descriptive research design. The method uses a survey with a cross sectional approach. The survey used a questionnaire as an instrument. The results of this study indicate that 92.4% of the sample has good knowledge, 95.25% of the sample knows that there is supervision in the use of PPE, and 89.5% of the sample has a good attitude. Conclusion: Most of the samples 92.4% have good knowledge, 95.25% know there is supervision in the use of PPE, and 89.5% have good attitudes.